Bacterial etiology and antibiotic resistance pattern of septicemia in HIV and non-HIV patients admitted to tertiary care hospitals, Shiraz, South of Iran - Ghassabi, F.; Hashempour, T.; Moghadami, M.; Davarpanah, M. A.; Kalani, M.; Chatrabnous, N.; Halaji, M.; Shahraki, H. R.; Hadi, N. (Cellular and Molecular Biology, 2017)
The present study aimed to determine the bacteriological etiology and antibiotic susceptibility pattern of sepsis in HIV infected and HIV uninfected patients, and related risk factors to introduce an appropriate therapy. This cross-sectional study was conducted from January 2014 to January of 2015 enrolling patients with sepsis associated with or without HIV infection admitted to Shiraz teaching hospitals, South of Iran. Blood and urine cultures were performed and standard microbiological methods were followed for isolation and identification of the bacteria. HIV antibody testing and CD4+ lymphocyte count were done for HIV-infected patients. Antimicrobial susceptibility tests were performed using the disk diffusion method in accordance with CLSI recommendations. Totally, 140 patients with sepsis including 30 HIV-positive, and 110 HIV-negative were enrolled. Our finding showed 26.7% and 20% blood and urine culture positivity in HIV-positive and 20.9% and 14.5% positivity in HIV-negative patients. Staphylococcus aureus, Salmonella spp. and coagulase-negative staphylococci (CoNS) each with frequency of 25% were detected as the most prevalent isolates in samples of HIV patients. In contrast, the main etiology for sepsis in HIV-negative patients was CoNS (47.8%), followed by Escherichia coli (17.4%). The median of CD4+ lymphocyte count and viral load in HIV patients were estimated 10.15 cells/mm3 and 68019.48 copies/mL, respectively. The results of the present study revealed that the main cause of sepsis in the studied hospitals was nosocomial pathogens. These findings highlighted the importance of infection control policies for preventing the emergence and spread of nosocomial infections.